(3GdfhQ GdeHjf def Yej Yf GdMb Gdjbjfs - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bGd CMeO Hf OMdGf(B: (3hCeG CMbjI NdGaI CHj HcQ abO fRdJ BjGJ bQBfjI ajgG GdETGQI Edi NdGaJg hLGAJ CMGOjK cKjQI JUQM hJTjQ Edi Pdc, aef GdBjGJs
(3BNQgG (B:s
(3BNQgG(B: (3hajg Yf GdebOGO Hf GdCShO(B: (3eYQaI id eMeO HQGAI ef GdfGQ, hMH id eMeO LhGR Ydi GdUQGW, hGdhdGjI dGd eMeO BeGf ef GdYPGH, Gddge GQRbfG Ydi eMHJge hhdGjJge hGQRbfG GdHQGFI ef CYOGFge heHZVjge hXGdejge aj GdOfjG hGdBNQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds